Guideline implementation in long term primary hypertension with diabetes management: an audit using a medication assessment tool in Selayang Hospital / Nik Mohd Fadhil Nik Mat - Nik Mat, Nik Mohd Fadhil (2009)
There are many guidelines was published via internet for references on management of hypertension. It has been suggested that guidelines developed at local level based on the available evidence from epidemiological studies and clinical trials would be most effective. Luckily, for Malaysian the Malaysia clinical practice guidelines on hypertension management was constantly reviewed and kept updated. Supposedly the adherence to this guideline should provide the best possible ways for hypertension management. However, do the Malaysia hypertension guidelines recommendation are being followed and practiced after being introduced to the local clinical setting? In reality, health providers should uses the relevant suggestions and recommendation within the hypertension guideline and apply it according to specific cases and conditions of individual hypertensive patients with diabetes. Development of this medication assessment tools (MAT) that based on local hypertension guideline seems to be ideal solution to evaluate hypertension management in Malaysia. Based on finding the total level of adherence to the guideline used is 62.9 %. This shows intermediate level of adherence for patients at diabetes MTAC of Selayang General hospital. Also, from findings it is found that there are 5 criteria showed high adherence to guideline, 5 criteria showed intermediate adherence and 5 criteria showed low adherence to guideline. For this study we only focused at finding the adherence level without determine the effects of this level of adherence towards hypertensive patients. Thus, it is suggested that we could conduct a future study that will evaluate the effects of level of adherence to hypertension guidelines towards hypertensive patients.